2008
DOI: 10.1017/s0952523808080280
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide polymorphisms upstream of the X-chromosome opsin gene array tune L:M cone ratio

Abstract: In support of the long-held idea that cone ratio is genetically determined by variation linked to the X-chromosome opsin gene locus, the present study identified nucleotide differences in DNA segments containing regulatory regions of the L and M opsin genes that are associated with significant differences in the relative number of L versus M cones. Specific haplotypes (combinations of genetic differences) were identified that correlated with high versus low L:M cone ratio. These findings are consistent with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…In the human retina, the expression of LWS cones exceeds that of MWS cones, and it has been suggested that opsin gene regulatory sequence variation, opsin gene proximity to the LCR, and the three-dimensional chromatin structure of the LWS / MWS locus may explain these differences [42,105-107]. As in the human LWS / MWS array, zebrafish RH2 opsin gene expression is also dependent on an LCR.…”
Section: Resultsmentioning
confidence: 99%
“…In the human retina, the expression of LWS cones exceeds that of MWS cones, and it has been suggested that opsin gene regulatory sequence variation, opsin gene proximity to the LCR, and the three-dimensional chromatin structure of the LWS / MWS locus may explain these differences [42,105-107]. As in the human LWS / MWS array, zebrafish RH2 opsin gene expression is also dependent on an LCR.…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that chromatin remodeling is an important component of L versus M cone differentiation (Knoblauch et al, 2006;Neitz et al, 2006;McMahon et al, 2008;Gunther et al, 2008). We propose that during gestation both L and M genes are active in each cone and the cell cycles randomly between transcription of either L or M opsin.…”
Section: Discussionmentioning
confidence: 99%
“…This explains the slight clumpiness that has been observed for the human L/M cone mosaic (Hofer, Carroll, Neitz, Neitz & Williams, 2005). Genetic changes in non-coding DNA in the region of the opsin genes are expected to influence how prone the DNA is to silencing and polymorphisms upstream of the opsin gene array have been found to be associated with individual differences in L/M cone ratio (Gunther, Neitz & Neitz, 2008, Stamatoyannopoulos, Thurman, Noble, Kutyavin, Shafer, Dorschner & Deeb, 2005). DNA is packaged as loops of chromatin in cells, and the most likely explanation for only two of the X-chromosome opsin genes being expressed is that the loop structures inhibit access of the LCR to opsin genes that are downstream of the first two genes in the array.…”
Section: Genes and The Cone Photoreceptor Mosaicmentioning
confidence: 99%